Der geteilte Himmel - Wolf, Konrad,Wolf, Gerhard,Brückner, Willi,Kuba,Wolf, Christa,Bergmann, Werner,Hosalla, Hans Dieter,Gründel, Dorit,Blume, Renate,Esche, Eberhard,Hardt-Hardtloff, Hans,Thate, Hilmar,Vogel, Peter (Suhrkamp [u.a.], 2009)
A woman in a big East German town suffers from injustice and suspicion when her fiancé runs away to the West, but is redeemed by an old and wise Party member.
Orig.: DDR 1964
Keywords: Feature films; Fiction films; Made-for-TV movies; Feature films - East Germany; Motion pictures - German language; Film; Man-woman relationships